Creating community-inclusive organizations: Managerial accountability framework - Fujimoto, Yuka *; Fara, Azmat; Nava, Subramaniam (Sage Publications, 2016)
Based on a community psychology perspective, this qualitative study explores the community inclusion effort of one of the largest pulp and paper companies in the world. Extending the literature on workforce diversity/inclusion, we present the community inclusive organizational framework, which signifies the dynamics of community inclusiveness of organizations highlighting key managerial accountabilities (i.e., cultural, collective, relational and structural accountabilities) based upon the community psychology perspective. Theoretical and practical implications are presented for promoting community inclusive organizations, along with avenues for further research.